The Apolipoprotein E ε4 Allele-Dependent Relationship Between Serum Lipid Levels and Cognitive Function: A Population-Based Cross-sectional Study - Wei, Shan; Gao, Ling; Jiang, Yu; Shang, Suhang; Chen, Chen; Dang, Liangjun; Wang, Jin; Huo, Kang; Wang, Jingyi; Qu, Qiumin (Frontiers in Aging Neuroscience, 2020)
Objectives: Till now, the effect of serum lipid levels on cognitive function is still controversial. The apolipoprotein E (APOE) ε4 allele is the most critical genetic risk factor for Alzheimer’s disease (AD) and cognitive impairment. Additionally, APOE ε4 allele has a major impact on lipid metabolism. The aim of this study was to investigate the APOE genotype-dependent relationship between peripheral serum lipid levels and cognitive impairment. Methods: A total of 1,273 subjects aged 40–86 years participated in this cross-sectional study. Serum lipid levels and the APOE genotype were detected. Mini-Mental State Examination was used to diagnose the cognitive impairment or not. Univariate and multivariate analyses were used to analyze the relationships between APOE genotype, serum lipid levels, and cognition function. Results: After controlling for all possible covariates, a significant interaction between low serum high-density lipoprotein and the APOE ε4 allele on cognitive impairment (Wald’s χ2 = 4.269, df = 1, OR = 20.094, p = 0.039) was found in the total participants. In APOE ε4 carriers, low serum high-density lipoprotein was positively associated with cognitive impairment (Wald’s χ2 = 8.200, df = 1, OR = 60.335, p = 0.004) and serum high-density lipoprotein levels were positively correlated with Mini-Mental State Examination score (r = 0.217, df = 176, p = 0.004). There was no significant correlation between serum total cholesterol (TC), low-density lipoprotein, triglycerides (TG) levels, and cognitive impairment in either the total participants or APOE ε4 carriers/non-carriers. Conclusions: APOE ε4 carriers, but not non-carriers, with lower serum high-density lipoprotein had a higher prevalence of cognitive impairment and a lower Mini-Mental State Examination score. These results suggest that the APOE ε4 allele may affect the relationship between serum lipid levels and cognitive impairment. However, the specific mechanism needs to be further elucidated.